Phenotypic and genotypic characterization of Staphylococcus spp with resistance to methicillin in commercial chickens - Cotaquispe, Rony (2021)
The study aimed to identify Staphylococcus spp with phenotypes and genotypes of methicillin resistance, as well as to identify variants of the coa + gene polymorphism in S. aureus. In total, 97 strains of Staphylococcus spp isolated from chickens were used and antibiograms and multiplex PCR, conventional PCR and sequencing tests were carried out. The phenotypic results indicate the presence of resistance to 2 MRSA and 26 SCN resistant to methicillin (cefoxitin) and 2 S. aureus and 67 SCN with presumed resistance to methicillin (oxacillin) in the antibiograms. Using PCR, the mecA gene responsible for methicillin resistance was identified in 24 strains: 2 MRSA and 22 SCNRM. In addition, 4 S. aureus genotypes with variants of the coagulase gene polymorphism were identified. The results suggest a constant genetic activity, the appearance of clones and the expression of genes for resistance to the main antibiotics faced by Staphylococcus spp.